Amartya Sen's Conception of Social Justice and Ethnic Crises in Contemporary Nigeria - Nwagbara, Rufus Godswill; Opafola, Sulaiman O.; Adefarasin, Victor O. (NIU Journal of Social Sciences, 2024)
Since the creation of the country called Nigeria, there has been debates on the issue of peaceful coexistence among the different ethnic groups in Nigeria. The nation has faced a series of ethnic, political, and economic crises, this has divided the ethnic lines bringing about disparities among the people. These disparities have raised rivalries due to the unequal distribution of the nation's resources. There are tensions arising from marginalisation of one ethnic group, at the expense of other ethnic groups, especially, minority ethnic groups. The marginalisation and dominance of a particular ethnic group in governance and leadership is daunting and challenging, and this has generated misunderstanding and mistrust among the people. As a result of this, the problem of ethnic relations is also affected due to a large number of ethnic groups in Nigeria. This brought ill feelings, hatred, injustice, imbalance, and intolerance among the people. In this regard, this paper adopts Sen’s Idea of Justice to end ethnic crises in contemporary Nigeria. This paper adopted analytical method and used the tool of critical analysis. This is to analyse ethnic crises and political instability in contemporary Nigeria. The ethnic crises is more compelling when viewed against the many occasions of injustice and unfair treatment suffered by the majority of marginalised, disadvantaged, and vulnerable minority ethnic groups in Nigerian society. This will pave the way for getting a clear understanding of why crises occurred in the country, gain some certainty of the facts, and establish the reasons and effects between those facts so that one can understand the relationships between variables which will help in getting solutions to the problems of ethnic crises in Nigeria. Findings revealed that Ethnic crises is one of the challenges facing the stability of Nigeria as a nation. It is on this premise that this research is based. Amartya Sen’s Idea of Justice will end the ethnic crises by adhering to it. Through Amartya Sen’s Niti and Nyaya, human reason can differentiate between justice and injustice through the realization process. Niti according to Sen is an idea of a just world, it is a procedural sense of justice and the instrument of codification. Nyaya is a comprehensive vision or design of realized justice. It represents the realistic and holistic sense of justice and focuses attention on the detailed result. The main task of Nyaya is preventing matsanyaya i.e. big fish-eating small fish which is an injustice. The study concluded that Ethnic crises have led to economic loss and rivalries between various ethnic groups. Contemporary Nigeria can end ethnic crises by adopting Amarya Sen’s Niti and Nyaya , and it is possible through Public Reasoning to end injustice among various Ethnic groups in contemporary Nigeria. The study therefore revealed that through Public Reasoning, it will eradicate ethnic crises and promote equality, unity, and peace.   Keywords: Ethnic crises, marginalization, ethnic group, Amartya Sen.